Facile and innovative catalytic protocol for intramolecular Friedel–Crafts cyclization of Morita–Baylis–Hillman adducts: Synergistic combination of chiral (salen)chromium(III)/BF3·OEt2 catalysis - Soundararajan, Karthikeyan; Jeyarajan, Helen Ratna Monica; Kamarajapurathu, Raju Subimol; Ayyanoth, Karthik Krishna Kumar (Beilstein Journal of Organic Chemistry, 2021)
The chiral (salen)Cr(III)/BF3·OEt2 catalytic combination was found to be an effective catalyst for intramolecular Friedel–Crafts cyclization of electron-deficient Morita–Baylis–Hillman adducts. In presence of mild reaction conditions the chiral (salen)Cr(III)/BF3·OEt2 complex affords 2-substituted-1H-indenes from unique substrates of Morita–Baylis–Hillman adducts via an easy operating practical procedure.
Keywords: boron trifluoride etherate; chiral (salen)chromium(III); intramolecular Friedel–Crafts cyclization; Morita–Baylis–Hillman adducts; substituted-1H-indenes